Soldaat en mens - Esterhuyse, Abel (Scientia Militaria - South African Journal of Military Studies, 2021)
In most paradigm militaries of the world, there seems to be an expectation for a general to write and publish his or her biography as soon as possible after retirement from active duty – a type of ‘first duty’ in retirement. These biographies are often critical for militaries, much like in the medical, law and clerical professions, to grow their body of knowledge and empower the next generation of soldiers. For armed forces in general, military history of this nature has always played an important role in the geographical and cultural contextualisation and shaping of their doctrine. Without a sound and comprehensive military historical foundation for the development of their doctrine, militaries remain dependent on the imported knowledge base of paradigm militaries.